2021
DOI: 10.3390/metabo11100690
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B and Cardiovascular Disease: Biomarker and Potential Therapeutic Target

Abstract: Apolipoprotein (apo) B, the critical structural protein of the atherogenic lipoproteins, has two major isoforms: apoB48 and apoB100. ApoB48 is found in chylomicrons and chylomicron remnants with one apoB48 molecule per chylomicron particle. Similarly, a single apoB100 molecule is contained per particle of very-low-density lipoprotein (VLDL), intermediate density lipoprotein, LDL and lipoprotein(a). This unique one apoB per particle ratio makes plasma apoB concentration a direct measure of the number of circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 275 publications
(306 reference statements)
5
100
0
4
Order By: Relevance
“…Experiments showed that RBIR values for PA decreased when HDL/LDL ratio was lower, indicating a reduction in HDL and/or an increase in LDL. Lower HDL/LDL ratios are a well-known marker of cardiovascular disease risk [52,53]. Thus, PA indicates that obese patients have significantly lower HDL/LDL ratios and, presumably, a higher cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments showed that RBIR values for PA decreased when HDL/LDL ratio was lower, indicating a reduction in HDL and/or an increase in LDL. Lower HDL/LDL ratios are a well-known marker of cardiovascular disease risk [52,53]. Thus, PA indicates that obese patients have significantly lower HDL/LDL ratios and, presumably, a higher cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation in the vascular endothelium of LDL particles enriched with cholesterol and lipoproteins that include ApoB is characteristic of ATS. All main atherogenic lipoproteins contain ApoB, which is an essential protein element [ 48 ]. Three mutations in the APOB-100 gene that determine ApoB-100’s lower affinity for receptors have been described using a molecular genetic technique [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both apoB48 and apoB100 are found in human aortic atherosclerotic plaques, indicating that TGRLs are involved in the formation of atherosclerotic plaque ( Nakano et al, 2008 ; Behbodikhah et al, 2021 ). Furthermore, the majority of apoB proteins isolated from human atherosclerotic plaques are derived from VLDL and IDL, but not LDL, suggesting that VLDL and IDL play a key atherosclerotic role in the intima of the arteries ( Rapp et al, 1994 ; Proctor and Mamo, 1998 ; Castillo-Núñez et al, 2022 ).…”
Section: Tgrl and Atherosclerosismentioning
confidence: 99%